ANALISIS PELAKSANAAN RESCHEDULING PEMBIAYAAN MURABAHAHPADA PT BPRS HAJI MISKIN PANDAI SIKEK - Yesti Marisa; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
The goal of this research is to prevent PT BPRS Haji Miskin Pandai Sikek from losing money on loans to banks and clients. This study employs a qualitative descriptive technique, which is a kind of inquiry that generates illustrative information by way of participants' own words or by direct observation of their actions in the field. The study's findings suggest that the causes of financial difficulties lie within the organisation. originating from the bank itself in analyzing financing that is not thorough and also caused by external factors originating from customers who are less able to manage operations. The rescheduling is carried out by the customer submitting a rescheduling to the BPRS Haji Miskin marketing party and the customer preparing a rescheduling submission requirement document in the form of the latest proof of income showing that the customer has experienced a decline and submitting it to the bank. After the customer submits the required documents to the bank, the marketing and internal audit departments will conduct a survey and analyze reliability of the customer's information in question. If the submitted documents have been declared complete and meet the criteria and have been approved by the committee, branch head and director, a rescheduling process can be carried out.